Semantic Changes in Information Communication Terms - Adiba Turahojaeva Khalilullaevna; Abdusattorova Farangiz (Indonesian Journal of Public Policy Review, 2022)
This article deals with linguistic changes in terms of ICT and their initial classroom teaching.